Suggestions for use of hypertonic saline solution with hyaluronic acid in cystic fibrosis patients - Volpi, S.; D'Orazio, C. (Acta Biomedica Atenei Parmensis, 2014)
The use of hypertonic saline (HS) is recommended in children (>6y) and adults with CF. ἀe ad-dition of HA is beneḀcial in CF patients who have previously shown poor tolerance to HS and may add an important anti-inᴀammatory eᰀect to this treatment.